Determination of the concentration-dependent effective diffusivity of CO2 in unconsolidated porous media saturated with heavy oil by considering the swelling effect. (February 2023) - Jang, Hyun Woong; Yang, Daoyong
Highlights: Concentration-dependent effective diffusivity of CO2 in an unconsolidated porous medium saturated with heavy oil is determined. Effect of oil swelling in a porous medium is implemented as well as it is theoretically estimated. Concentration profiles of CO2 generated by concentration-dependent and constant effective diffusivities are compared. Concentration-dependent effective diffusivity of CO2 in heavy oil which saturates a porous medium may be converted to its molecular diffusivity of CO2 in the same bulk heavy oil through the diffusive tortuosity, and vice versa. Abstract: Effective diffusivity of CO2 in the unconsolidated sandpack saturated with a Lloydminster heavy oil was determined in the form of an exponential function of CO2 concentration in the diluted and swollen liquid-phase. For such a purpose, two pressure-decay experiments were executed at different pressure ranges (i.e., 855–817 kPa and 1993–1905 kPa) and a temperature of 299.65 K. First, the sandpack saturated with heavy oil was prepared under an increased temperature of 348.15 K because the reduced heavy oil viscosity was required to saturate the sand column with heavy oil in a diffusion cell. Next, the diffusion cell containing the Lloydminster heavy oil-saturated sand column was integrated into a pressure-decay experimental system with pressure-monitoring devices. Then, pressure-history curves of both the diffusion experiments were continuously recorded to be compared with the theoretically calculated ones. The Fick's 2nd law incorporated with the volume-translated Peng-Robinson equation of state (PR-EOS) was implemented to determine the concentration-dependent effective diffusivity of CO2 in a sandpack saturated with heavy oil considering its swelling effect through minimizing the deviations between the theoretically computed pressure-history curves with the experimentally recorded ones. For the computation of the Fick's 2nd law, the Crank-Nicolson scheme finite difference method (FDM) was applied to take the local oil swelling into account for enhancing the accuracy of such a determined diffusivity. The excellent agreements between the theoretically computed and experimentally measured pressure-history curves at both the pressure ranges signify that such a determined effective diffusivity considering the CO2 concentration is accurate and reliable.